CONTINUING TRAINING AND CONSTRUCTION OF CONCEPTS ABOUT LITERACY AND LITERACY - Portos Rodrigues, Charles; José Pereira, Benedito (Revista Gênero e Interdisciplinaridade, 2024)
Literacy and literacy are constant concepts in the daily life of the teacher who introduces the first contact with reading and writing into the student’s life. These concepts differ in the context of the appropriation of language and writing, but one complements the other. Due to the confusing understanding of the effect of these two concepts, continuing education appears as a bridge of clarification and job training for the education professional with resources that promote both the student’s performance in writing, reading and understanding. With the aim of demonstrating the main difficulties of the literacy teacher in the pedagogical process of literacy, when inserted into literacy and the importance of continued training for clarification and qualification of the same, the present work proposes to expose and discuss the proposals of some training programs , in the light of the theories of (SOARES, 2003), (FREIRE, 1989), (FALSARELLA, 2004), among others, aiming to improve the training of literacy teachers and their interaction with new literacy methodologies.